Potency of Actinomycetes from Deepsea Sediment of Makassar Strait for Producing Antimicrobial Substances - Ariani Hatmanti; Puspita Lisdiyanti; Jaka Widada; Subagus Wahyuono (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2018)
A study on isolation of actinomycetes from sediments of Makassar Strait have been conducted with regard to research project called Widya Nusantara Exploration (EWIN) in May-June 2013 and November 2014. The objectives of this research were to screen antimicrobial activity of 36 actinomycetes from sediments of Makassar Strait, characterized the potential isolates, and determined the metabolites produced by the selected isolate. The antimicrobial screening was conducted using agar diffusion method, while characterization of the best five of actinomycetes were using APIZYM Kit, Scanning Electron Microscope, and FTIR. Five isolates retrieved from this research had ability to inhibit the growth of four microbial testing: Escherichia coli, Bacillus subtilis, Staphyllococcus aureus and Candida albicans. The highest capability was shown by the MACMK-43 isolate that had 16S rRNA gene sequence similarity of 97.85% to Streptomyces violacens. The result shows that, the active fraction contained of 4-amino-5-cyano-6-(4’methoxyphenyl)-1-methyl-2.3-dihydropyrrolo [2,3-B] pyridine, which is commercially used for bactericide and antihistamine.